2019
DOI: 10.1200/jco.2019.37.4_suppl.420
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of RX-3117, an oral antimetabolite nucleoside, in combination with nab-paclitaxel (nab-pac) as first-line treatment of metastatic pancreatic cancer (met-PC): Preliminary results.

Abstract: 420 Background: RX-3117 is an oral small molecule antimetabolite, cyclopentyl pyrimidyl nucleoside that is activated by cancer-enriched uridine cytidine kinase 2. Single agent RX-3117 has demonstrated efficacy in a phase III single agent clinical study of RX-3117 in met-PC and bladder cancer. RX-3117 in combination with nab-pac is being evaluated as first line treatment of met-PC cancer. Methods: This is a multicenter, open label phase I/II study (NCT03189914). Eligible subjects (aged ≥ 18 years) have histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…weekly) for 3 weeks with one week off in patients with metastatic pancreatic cancer [37]. Preliminary updated data (Clinical Trial number NCT03189914; Jan 2019 [38]) revealed a disease control rate of 92% (22/24 patients) at 8 weeks, including a CR after 6 cycles of therapy, 8 PR and 13 SD [38]. PK analyses indicated that RX-3117 and nab-paclitaxel did not interfere with each other, with comparable Cmax and AUC for RX-3117 as in the single-agent study.…”
Section: Phase I and Ii Studies And Pharmacokineticsmentioning
confidence: 99%
“…weekly) for 3 weeks with one week off in patients with metastatic pancreatic cancer [37]. Preliminary updated data (Clinical Trial number NCT03189914; Jan 2019 [38]) revealed a disease control rate of 92% (22/24 patients) at 8 weeks, including a CR after 6 cycles of therapy, 8 PR and 13 SD [38]. PK analyses indicated that RX-3117 and nab-paclitaxel did not interfere with each other, with comparable Cmax and AUC for RX-3117 as in the single-agent study.…”
Section: Phase I and Ii Studies And Pharmacokineticsmentioning
confidence: 99%
“…We have reported here a new methodology for the synthesis of polymers of nucleoside-mimetic drugs by TcEP. , The development of this simple and potentially scalable synthetic methodology was motivated by the observation that nucleoside drugs such as 5FU and gemcitabine are currently used to treat solid tumors ,, and that several nucleoside and nucleotide analog drugs are currently in clinical trials for treatment of various cancers. Unfortunately, these drugs have a high IC 50 and a narrow therapeutic window, thus methods to deliver a high drug payload to tumor cells to enhance its efficacy and avoid systemic toxicity are clearly needed. To increase the payload of such drugs, polymerization of prodrugs or encapsulation in nanoparticles (NPs) are common approaches.…”
Section: Discussionmentioning
confidence: 99%